Inventory of Ectoparasites in Majalaya Carp (Cyprinus carpio) With Different Sizes - Umar, Putra Arif Yanto; Lamadi, Arafik; Ahmad, Indra G (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Majalaya carp (Cyprinus carpio) is one of the essential commodities used to increase fisheries production in Indonesia. However, this cultivation activity is often hampered by disease problems caused by parasites. Therefore, it is necessary to research the inventory of ectoparasites in Majalaya carp with different sizes. This study aims to determine the type, intensity, and prevalence of ectoparasites in Majalaya carp of different sizes. Samples were taken by random sampling from cultivation ponds in the North Minahasa Regency, North Sulawesi Province. The research method used a descriptive method, and for ectoparasite examination, a native method was used by examining the surface of the fish's body, mucus, fins, gills, and eyes. The study results found six types of ectoparasites: Dactylogyrus sp, Argulus sp, Ichthyophthirius multifiliis, Trichodina sp, Vorticella sp, and Gyrodactylus sp. At a size of 4-7 cm, more Dactylogyrus sp were found. On the gills, size 8-14 cm I. multifiliis on mucus and size 23-30 cm Argulus sp on the surface of the fish body. The intensity level of ectoparasites produced on Dactylogyrus sp reached a value of 5.14 Ind/fish (low infection), I.multifiliis 4.27 Ind/fish (low infection), and Argulus sp of 3.80 Ind/fish (low infection). Then, the prevalence level of ectoparasites produced on Dactylogyrus sp reached a value of 70% (moderate infection), Ichthyophthirius multifiliis 50% (persistent infection), and Argulus sp 67% (persistent infection). This study emphasizes the importance of water quality management and fish density regulation.